Words beyond meaning in Mapuche language ideology. (November 2018) - Course, Magnus
Abstract: What is the difference between the Mapuche language, Mapudungun, and Spanish? Perhaps the term "difference" is a clue to the approach from which my thinking on this topic has emerged. For in using the term "difference" I follow a particular genealogy of anthropologists who have asked the question of whether our difference is the same kind of difference as theirs, with "ours" and "theirs" themselves being relative constructs. Our question thus becomes a question about a question: are we asking whether Mapudungun and Spanish are two different kinds of the same thing? Or are we asking if they are two different things? I suggest that ultimately both questions are pertinent to my Mapuche interlocutors' thinking on this topic. Highlights: Addresses nature of linguistic difference beyond language ideology alone. Seeks to apply a comparative relativist framework to questions of multilingualism and differences between language. Applies insights from social and cultural anthropology to linguistic anthropology in the context of indigenous South America.